The Whistleblowing Diamond: Considering Four Elements of Whistleblowing Intention - Dwi Defiantoro (Profesional Muda Cendekia Publishing, 2023)
We review how whistleblowing diamond factors affect whistleblowing intention which are moderated by perceived organizational support. This quantitative research was conducted using a case study survey method with a sample of 220 village officials in Minahasa Regency. This study uses the whistleblowing diamond theory, which explains four type of factors that can influence a whistleblower's intention to conduct whistleblowing, namely: pressure/incentives, opportunity, rationalization, and capability. This study found that the factors that significantly influenced whistleblowing intentions were opportunity, rationalization, and capability with a significance of p<0.05, 0.001, 0.004, and 0.033, respectively. Meanwhile, pressure and incentive factors proved not to significantly affect whistleblowing intentions, with a significance value of p>0.05, 0.779, and 0.924, respectively. This study also found that the moderating factor of perceived organizational support increased the influence of pressure, incentives, opportunity, rationalization, and capability on the intention to report violations with a significance value of 0.0001 to 0.005.